Individual Business Plan: “Center for Environmental Education and Development” (CEED) - Moirangthem, Ajanta Singh (2013)
The sense of a need to take up responsibilities and take initiatives in addressing less served social aspects has motivated several entrepreneurs to start up social enterprises. The following project proposal is a model of a social enterprise which tries to spread environmental awareness among the youths, students and various communities through its various activities. The organization seeks to capitalize on the vast bamboo resources of the state of Manipur (India) and its neighbouring North-Eastern states to take up a business model of manufacturing paper from bamboo. This organization will also incorporate recycling paper unit which will also be used as a medium in its line of environmental education. The strategy of the organization will mainly be based on the concept of entrepreneurial marketing with a scope to garner creativity and innovativeness to enthuse the organization in its quest for a social mission with a social vision.